Dwufazowy przepływ powietrza i wody w pionowych wyrobiskach górniczych - Branny, Marian; Filek, Krzysztof; Nowak, Bernard; Ptaszyński, Bogusław (My University, 2008)
The article describes examples of two-phase flows in mining excavations and its impact on ventilation systems. Author discusses some of flows features, parameters and its theoretical models. The article presents computational model of two-phase flows in vertical expiratory shaft, using Euler-Lagrange's method. Numerical simulations were performed with the discrete phase model implemented using computational fluid dynamics (CFD) software- Fluent. Calculations results presented in the form of graphs are enclosed.

W artykule opisano przykłady występowania przepływów dwufazowych w wyrobiskach górniczych i ich możliwy wpływ na przewietrzanie. Określono niektóre cechy takich przepływów, ich parametry oraz modele ich teoretycznego opisu. Przedstawiono wyniki badań numerycznych w pionowym szybie wydechowym, przyjmując metodykę opisu Eulera-Lagrange'a. Posługując się modelem fazy rozproszonej (the discrete phase model), zaimplementowanym w oprogramowaniu Fluent wykorzystującym wspomnianą metodykę, wykonano pierwsze próby numerycznych obliczeń. Wyniki zamieszczono w postaci wykresów.
Two-phase flow of air and water in mining excavators
Górnictwo i Geoinżynieria
Bibliogr. s. 22.
Keywords: two-phase flow; przepływy dwufazowe; flow in ventilating shaft; przepływ w szybie wentylacyjnym; numerical simulations the two-phase flows; symulacje numeryczne przepływów dwufazowych; model of discrete phase; model fazy dyskretnej